LIFE CICLE AND HABITS OF Bracon kirkpatricki (Wilkinson) (Hymenoptera: Braconidae) - LEÓN-M., GUILLERMO A.; ERAZO-G., ANA LUCÍA (Revista Colombiana de Entomología, 1993)
The Life cycle and habits of Bracon kirkpatricki (Wilkinson) were studied and a fertility table was constructed. The studies we re conducted at the ICA Entomology laboratory in Palmira (T.24°C; R.1-1.=73`1/0). The hosts utilized to rear the parasitoid were larvae of Ephestía kuehniella (Zeller). The incubation period was 23.5 hours; the larvae showed five instars and a total duration of 6.7 days; the pupa) period averaged 4.49 and 4.56 days for male and female, respectively. Adult females lived an average of 29.4 days and males 27.8 days. The preoviposition period was 2.5 days and the oviposition period was 15 days. Total fecundity was 38.6 eggs per female with an average of 1.4 eggs per day. Time until 50% death of the population was 25 days.